The heat energy dissipated in a control volume to correlate the crack propagation rate in stainless steel specimens - G. Meneghetti; M. Ricotta (Fracture and Structural Integrity)
Metallic materials dissipate thermal energy when subjected to fatigue. Some of them, due a favorable combination of thermo-physical material properties, exhibit a significant temperature rise, which can be easily measured in-situ by means of thermocouples or infrared cameras. The heat energy dissipated in a unit volume of material per cycle (the Q parameter) has proven to be effective as a fatigue damage index in case of AISI 304L plain and notched specimens. Originally conceived and applied as a point-related quantity, recently Q has been averaged at the tip of propagating fatigue cracks (the Q* parameter) in order to correlate crack growth data gathered from fracture mechanics tests. The use of Q* seems interesting because (i) it can be evaluated in-situ from infrared temperature maps and (ii) crack acceleration due to excessive plasticity is likely to be accounted for.